MOLECULAR DOCKING ANALYSIS OF THIRTEEN COMPOUNDS AS MODULATOR OF IONOTROPIC GLUTAMATE RECEPTOR - Narayanaswamy, Radhakrishnan; Hailu, Merry (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Ionotropic glutamate receptors (iGluRs) play a key role in the development and function of the nervous system. They also play an important in memory and learning process. They are implicated in various pathological conditions such as Alzheimer's, Epilepsy, Huntington's, and Parkinson's diseases. This prompted us to carry out the present study on 13 selected compounds. Methods: These 13 compounds were evaluated on the docking behavior of iGluR-2 (iGluR2) using PatchDock. In addition, molecular physicochemical, drug-likeness, absorption, distribution, metabolism, and excretion analyses were also carried out. Results: The molecular physiochemical analysis revealed that all the 13 ligands showed nil violation and complied well with the Lipinski's rule of five. ADME analysis showed that all the ligands (except ligands 1 and 12) predicated to have high gastrointestinal absorption property. Docking studies revealed that ligand 8 (dopamine) showed the highest atomic contact energy (ACE) (âˆ’78.14 kcal/mol), while ligand 9 (6-hydroxydopamine) showed the least ACE (âˆ’14.34 kcal/mol) with that of iGluR2. Similarly, ligand 8 (dopamine) has shown to interact with Ser 142 amino acid residue of iGluR2. Conclusion: Thus, the present study showed the potential of 13 compounds as a modulator of iGluR-2.